Spontaneous uterine rupture of an unscarred uterus in primigravida: case report - Bansode, Minakshi D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
A spontaneous rupture of the unscarred uterus in a primigravid patient is extremely rare and is associated with high perinatal and maternal morbidity and mortality. Study report a case of spontaneous rupture of an unscarred uterus at 36 weeks of gestation in a 22-years primigravid woman. Ultrasonography showed posterior low-lying placenta praevia with lower margin touching internal OS. Operative findings during emergent caesarean section revealed e/o 2 L of hemoperitoneum, uterus was bicornuate and pregnancy was in the right horn. There was fundal rupture of right horn measuring approximately 6-7 cm anteroposterior. Incision was taken on the lower part of right horn and placenta was seen on anterior wall. Baby delivered as breech after incising placenta. Postoperative recovery was uneventful. In, conclusion, bicornuate uterus may be an independent risk factor for uterine rupture, which can occur in primigravid patients and at any gestation.